VIRUS-SPECIFIC HUMORAL IMMUNE RESPONSE ISOTYPIC STRUCTURE IN ADULT PATIENTS HOSPITALIZED WITH INFLUENZA A - V. Z. Krivitskaya (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
The aim of this investigation was a comparative analysis of isotypic structure of specific antiviral systemic humoral immune response in hospitalized patients with influenza caused by virus A(H3N2) or A(H1N1), including the A(H1N1)pdm09. Paired acute and convalescent phase sera from 109 adult patients aged 18 to 67 years with laboratoryconfirmed influenza A were analyzed by ELISA. Purified surface glycoproteins of influenza A viruses of different subtypes containing the hemagglutinin and neuraminidase were used as antigen for sensitization of plates in ELISA.The absence of type-specific conserved internal proteins in antigenic material allowed to carry out a subtype-specific differentiation of antibodies against influenza viruses in ELISA. Regardless of the subtype of influenza A viruses caused the disease, the most pronounced response was observed by subtype-specific IgG1 (70–90% of seroconversions). It has been shown for the first time that low activity of virus-induced IgG2 (6–9% of seroconversions) is a peculiarity of the immune response both to primary or recurrent infections with A(H1N1)pdm09. In patients repeatedly suffered by «seasonal» influenza A(H1N1) in 2007/2008 or influenza A(H3N2) in 2012–2014 IgG2 seroconversion’s rates were 40–59% (р < 0,05). Reaction virusspecific IgG3 was also weaker in patients with influenza A(H1N1)pdm09 (29–44% of seroconversions) than in subjects with influenza A(H1N1) or A(H3N2) (65% and 56% of seroconversions, respectively). Geometric mean titers of virus neutralizing antibodies identified during recovery phase in patients with primary and secondary influenza A(H1N1)pdm09 (1/28 and 1/103, respectively) were significantly lower than in patients recovered from influenza A(H1N1) or A(H3N2) (GMT were 1/594 and 1/378, respectively). It was shown that the surface glycoproteins of influenza A viruses may be an allergens. Virus-specific IgE seroconversion rates were comparable in all groups reaching 25–45%. The high activity of virus-induced serum IgA was detected in patients with influenza A(H3N2) or A(H1N1)pdm09 (60–79% of seroconversions). Thus, study of virus-specific activity of various immunoglobulin isotypes provides important information about the formation of adaptive antiviral immune response to influenza A viruses, and also estimate the contribution of its protective and immunopathogenic components to pathogenesis of the disease.